The application of multi-layer phosphor-in-glass sheets in boosting white light emitting diodes chromaticity - Ha Thanh Tung; Huu Phuc Dang; Nguyen Le Thai (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
With the use of phosphor-in-glass (abbreviated as PiG), it is possible to make alterations for the remote adjustment incorporated with a diode that generates blue light emitting diode (LED) and acquire remarkably superior light output at considerable temperatures of color compared to standard structures of LED devices. It should be noted that the imbrication of emission spectra in phosphor substances, as well as the forfeited, amount of light caused by reabsorption appear to be the primary problems stemming from the model of multi-color phosphor. The earlier study came up with the method of creating various phosphor-in-glass (PiGs) by slicing and reconstruction, which remedied certain aspects of the flaws mentioned. Practically speaking, the light amount forfeited occurs in the linking zones in the middle of the color phosphor and will be a subject of the research. We can see for certain that it is necessary to come up with a means of preparation to deal with the issues of the interfacial layer. Therefore, the low sintering of PiGs at 600 °C was considered an appropriate procedure, as it could create a double-layer PiG in a lying direction as well as a triple-layer PiG yielding superior optical efficiency when compared to equivalent versions.